Pengaruh Irigasi Terhadap Kelangkaan Sumber Daya Air, Produktifitas dan Pendapatan Petani di Desa Klepek Kecamatan Sukosewu Kabupaten Bojonegoro - Budi Santoso; Nurul Badriyah; Hagus Tarno; Fitri Candra Wardana (Postgraduate, University of Mataram, 2025)
This research aims to investigate the impact of irrigation in addressing water scarcity, improving productivity, and increasing farmers' income in Klepek Village, Sukosewu Subdistrict, Bojonegoro Regency. Agriculture productivity is influenced by factors such as the efficient use of resources such as water. The availability of irrigation water is crucial to enhance agricultural productivity. Water scarcity can hinder plant growth, reduce crop yields, and negatively impact farmers' economies. Farmers faced serious challenges regarding water availability for agriculture in Klepek Village. In this study, the researcher conducted interviews, observations, and collected data to describe and analyze the impact of irrigation on addressing water scarcity, improving productivity, and increasing farmers' income in Klepek Village, Sukosewu Subdistrict, Bojonegoro Regency. A SWOT analysis was used to set an effective strategy of water management in order to improve the irrigation system. The sample reserach consisted of 30 respondents. A SWOT analysis indicate the position of quadrant I. It implies an aggressive strategy: improving famers skills in both, technical abilities and management skills. The results of the research indicate that irrigation has successfully become an effective solution to address water scarcity, leading to increased agricultural productivity and crop diversification.